The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.25081/josac.2017.v26.i1.809
|View full text |Cite
|
Sign up to set email alerts
|

Response of fenugreek (Trigonella foenum-graecum) to bio-regulators TGA and N-acetyl cystein under drip irrigation levels

Abstract: Field experiments were conducted during winter seasons of 2010-11 and 2011-12 at Bikaner (Rajasthan) to study the effect of bioregulators viz., TGA and N-acetyl cystein under different drip irrigation levels on yield, yield attributes, water use and water use efficiency of fenugreek. The highest plant height (69 cm) and yield attributes viz., branches plant -1 (7.6), pods plant -1 (46.3), pod length (13.5 cm), seed pod -1 (16) and test weight (12.7 g) were recorded with 100% ETc + TGA (200 ppm). Further, 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The highest plant spread (North -South) and (East -West) at 30, 60, 90 days after sowing and harvest stage was recorded in T10 -50% RDN through FYM (8 t ha -1 ) + 50% RDN through Neem cake (1 t ha -1 ) + 50% RDN through Vermicompost (2 t ha -1 ) + AMC (7.5 lit ha -1 ) might be due to the same treatment registered maximum plant height and more number of branches per plant as compared to rest of the treatments. The results are similar with the findings of Khiriya et al (2001) [5] , Aiyanathan and Salairajan (2008) [1] in fenugreek and Naveen (2010) [9] in kasuri methi.…”
Section: Growth Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…The highest plant spread (North -South) and (East -West) at 30, 60, 90 days after sowing and harvest stage was recorded in T10 -50% RDN through FYM (8 t ha -1 ) + 50% RDN through Neem cake (1 t ha -1 ) + 50% RDN through Vermicompost (2 t ha -1 ) + AMC (7.5 lit ha -1 ) might be due to the same treatment registered maximum plant height and more number of branches per plant as compared to rest of the treatments. The results are similar with the findings of Khiriya et al (2001) [5] , Aiyanathan and Salairajan (2008) [1] in fenugreek and Naveen (2010) [9] in kasuri methi.…”
Section: Growth Parameterssupporting
confidence: 92%
“…(2001) [5] , Kumawat et al (2003) [6] , Raiyani et al (2018) [11] and Rakesh et al (2019) [12] in fenugreek and Agarwal et al…”
Section: Growth Parametersmentioning
confidence: 99%
“…Several studies on other plants illustrated that the maternal habitat [ 43 46 ] and seed priming [ 47 – 49 ] influence offspring adaptive plasticity to tolerate abiotic stresses. Furthermore, previous research on fenugreek reported its ability to withstand a wide range of sodicity at various growth stages [ 50 53 ]. Altogether, they illustrate the power of our population to grow in the newly reclaimed saline sandy soil irrigated with saline water in Wadi, as most of the genotypes were collected from Upper Egypt, Alexandria, Faiyum, and Ismailia governorates with sandy soil of different degrees of salinity.…”
Section: Discussionmentioning
confidence: 99%
“…The irrigation water use efficiency depends on irrigation level. Irrigation scheduling provides water to the plants, which matches the crop evapotranspiration rate and provides optimum irrigation at critical growth stages, resulting in high water use efficiency (Mehta et al, 2010). This increase in water saving might be due to the efficient use of water, which was applied to maintain the appropriate soil moisture along with the maximum yield obtained with the minimum quantity of water.…”
Section: Effect Of Irrigation Regimes On Water Use Efficiency and Wat...mentioning
confidence: 99%
“…However, it was found at par with application of 100 % RDF (38.3 kg ha-mm -1 ) and (3.83 kg m -3 ) of kalonji. The higher water use efficiency and water productivity with higher level of fertilizer might be due to a greater increase in seed production (Mehta et al, 2010). Under lower fertilizer levels obtained lower water use efficiency and water productivity due to low availability of nutrients, which resulted in higher water use but minimum economic yield.…”
Section: Effect Of Fertility Levels On Water Use Efficiency and Water...mentioning
confidence: 99%